2002
DOI: 10.1002/acp.917
|View full text |Cite
|
Sign up to set email alerts
|

The influence of test‐set similarity in verbal overshadowing

Abstract: The verbal overshadowing effect is the phenomenon in which describing a previously seen face impairs its recognition (Schooler and Engstler-Schooler, 1990). The primary purpose of this research was to investigate how the similarity between a target and distractors influences verbal overshadowing. In order to manipulate test-set similarity, we blended the faces of different people by using morphing techniques. As a result, verbal overshadowing was found when test-set similarity was relatively high, while the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
(30 reference statements)
4
33
0
Order By: Relevance
“…Although interference theory was developed mainly for verbal material, many studies have indicated that visual similarity interferes with recognition of visual figures and faces (e.g., Baddeley, 1976;Kitagami, Sato, & Yoshikawa, 2002;Tulving, 1981;Wells, 1988). Many researchers have found that looking at pictures of faces during the interval between learning and testing of the target face interferes retroactively with its recognition.…”
Section: Methodsmentioning
confidence: 99%
“…Although interference theory was developed mainly for verbal material, many studies have indicated that visual similarity interferes with recognition of visual figures and faces (e.g., Baddeley, 1976;Kitagami, Sato, & Yoshikawa, 2002;Tulving, 1981;Wells, 1988). Many researchers have found that looking at pictures of faces during the interval between learning and testing of the target face interferes retroactively with its recognition.…”
Section: Methodsmentioning
confidence: 99%
“…Semantic images of target and distractors are shown in Figure 1 . In the recognition phase, it was necessary to present eight images (the target and distractors) in one page to imitate the form of photo lineup ( Schooler & Engstler-Schooler, 1990 ;Kitagami, et al ., 2002 ). In the encoding phase, only the target face was presented in one page and the target face needs to be observed carefully by participants.…”
Section: Methodsmentioning
confidence: 99%
“…This allowed manipulation of whether the verbally described features were distinguishing (modifi ed) features between target and distractors. A single target face was used because most verbal overshadowing studies use one test set ( Finger & Pezdek, 1999 ;Finger, 2002 ;Kitagami, et al ., 2002 ;Itoh, 2005 ). All stimuli were presented in gray scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations